2019
DOI: 10.1016/j.celrep.2019.08.073
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Pan-Id Antagonist Inhibits Pathologic Ocular Neovascularization

Abstract: SUMMARY Id helix-loop-helix (HLH) proteins (Id1–4) bind E protein bHLH transcription factors, preventing them from forming active transcription complexes that drive changes in cell states. Id proteins are primarily expressed during development to inhibit differentiation, but they become re-expressed in adult tissues in diseases of the vasculature and cancer. We show that the genetic loss of Id1/Id3 reduces ocular neovascularization in mouse models of wet age-related macular degeneration (AMD) and retinopathy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 61 publications
3
55
0
1
Order By: Relevance
“…We tested whether AGX51 would have similar effects on pancreatic cancer cells. In line with the results obtained in other cancer models that we tested, AGX51 caused a depletion of the ID1 and ID3 proteins in the pancreatic cancer cell line 806, starting at a dose between 4 and 20 µM ( Figure 3A) with ID3 showing slightly less sensitivity as observed in other cellular and biophysical assays (Wojnarowicz et al, 2019). Furthermore, AGX51 decreased cell viability in a variety of pancreatic cancer cell and organoid lines, including mouse organoids ( Figure 3B), mouse cell lines 806, NB44, and 4279 ( Figure 3C), and human cell lines Panc1 and A21 ( Figure 3D) with an IC50 of 5.5-19.5 µM.…”
Section: Effects Of Agx51 On Cell Growthsupporting
confidence: 90%
See 4 more Smart Citations
“…We tested whether AGX51 would have similar effects on pancreatic cancer cells. In line with the results obtained in other cancer models that we tested, AGX51 caused a depletion of the ID1 and ID3 proteins in the pancreatic cancer cell line 806, starting at a dose between 4 and 20 µM ( Figure 3A) with ID3 showing slightly less sensitivity as observed in other cellular and biophysical assays (Wojnarowicz et al, 2019). Furthermore, AGX51 decreased cell viability in a variety of pancreatic cancer cell and organoid lines, including mouse organoids ( Figure 3B), mouse cell lines 806, NB44, and 4279 ( Figure 3C), and human cell lines Panc1 and A21 ( Figure 3D) with an IC50 of 5.5-19.5 µM.…”
Section: Effects Of Agx51 On Cell Growthsupporting
confidence: 90%
“…Id3 and Id4 are also lost albeit with delayed kinetics. Id2 is not expressed in 4T1 cells (data not shown) but we previously showed that ID2 levels decrease in response to AGX51 treatment in HCT116 cells (Wojnarowicz et al, 2019). Similar to 4T1 cells, HMLE RAS Twist cells (immortalized human mammary epithelial cells overexpressing Twist) also showed reduced levels of ID1, ID3 and ID4 when treated with 20 μM AGX51 over similar time courses ( Figure S1B).…”
Section: Effects Of Agx51 On Id Proteinsmentioning
confidence: 55%
See 3 more Smart Citations